Intermittent milling and dynamic steeping process for corn starch recovery - Lopes-Filho, J. F. [UNESP]; Buriak, P.; Tumbleson, M. E.; Eckhoff, S. R. (Wiley, 1997)
A procedure that reduces diffusional limitations by periodically milling the corn to reduce particle size and stirring the ground mash in the presence of sulfur dioxide (SO2) and lactic acid was developed. The process, called intermittent milling and dynamic sleeping (IMDS), includes three main stages: initial soaking (a short-time immersion in water) of whole kernels, initial cracking of the partially hydrated kernels, and dynamic sleeping with interspersed milling. This study evaluated the three stages of the process separately, evaluating the effect of variables on each stage of the process. Corn fractions yield (germ, fiber, gluten, attach) were used to decide the best conditions for the soaking and sleeping stages, and germ damage was used to determine the best kernel cracking method. Starch, gluten, and germ yields were not affected by soak temperatures (52-68°C) or soak time (1-3 hr). A temperature of 60°C was chosen for soaking because it increased the rate of kernel hydration without gelatinizing starch, which happens at higher temperatures. A 2-hr soak time was preferred because there was less fiber in the germ fraction and less germ damage was observed. Although there were no advantage to using SO2 or lactic acid in the soak water, the presence of these compounds during dynamic steeping enhanced starch yield. The starch yield for 3 hr of dynamic stooping was not statistically different from the starch yield for a 7.5-hr dynamic steep. The Bauer mill was preferred over the use of a roller mill or a commercial grade Waring blender for kernel cracking. The IMDS process produced, on an average, 1 percentage point more starch than the conventional 36-hr stooping process. Total steep or kernel preparation time was reduced from 24-40 hr for conventional wet-milling to 5 hr for the IMDS process.